PENGUKURAN KONSTANTA DISOSIASI ASAM MONOETHANOLAMINE PADA SUHU 30-60°C - Eleonora Amelia; Deasy R. Alwani; Sholeh Ma’mun (Teknoin, 2016)
Global warming caused by greenhouse gas emissions, e.g. carbon dioxide (CO2), in the atmosphere is now becoming a very serious problem facing the world community. Carbon dioxide emission increase from year to year, thus a necessary effort to reduce CO2 is required. Amine-based absorption is one of the methods for post-combustion capture. Monoethanolamine (MEA) is commonly used for CO2 capture solvent. This study aims to measure protonation constant (pKa) of MEA from 30 to 60°C using the potentiometric titration method. The results show that the pKa values of MEA are in general agree with the literature data. For instance, the pKa value of MEA at 30°C is 9.83 and that obtained from the literature is 9.80. Comparison between those two values gives a deviation of 0.22%.